Driving Errors in Persons with Dementia. Issue 7 (3rd July 2015) - Barco, Peggy P.; Baum, Carolyn M.; Ott, Brian R.; Ice, Steven; Johnson, Ann; Wallendorf, Michael; Carr, David B.
<x xml:space="preserve">Abstract</x> Objectives To differentiate driving errors in persons with dementia who fail a performance‐ based road test from errors in persons who pass. Design Cross‐sectional. Setting Community. Participants Active drivers diagnosed with dementia (n = 60) and older adult controls (n = 32). Measurement All participants completed a standardized clinical and on‐road driving assessment. The outcome variable was the number and types of driving errors according to the Record of Driving Errors (RODE), a standardized tool to record driving errors. Results Sixty‐two percent (n = 37) of individuals with dementia and 3% (n = 1) of controls failed the road test. Based on the RODE, individuals with dementia made twice as many driving errors as healthy controls. Within the dementia sample, individuals who failed the road test had more difficulties driving straight and making left and right turns than during lane changes. Dangerous actions occurred most often while driving straight and making left turns. Specific driving behaviors associated with road test failure in the sample with dementia included difficulties in lane positioning and usage, stopping the vehicle appropriately, attention, decision‐making, and following rules of the road. Informants of participants with dementia who failed the road test reported more impairment with cognitive functioning on the Assessing Dementia 8 Screening Interview (AD8). Conclusion This report highlights the driving errors most common in people with dementia who fail a road test. The finding that most of the dangerous actions in the sample with dementia occurred while driving straight condition is novel. Driving on straight roads has not been considered a condition of "high challenge" in prior driving studies in individuals with dementia. This finding has potential implications for future interventions related to vehicle instrumentation and driving recommendations for people with dementia.